Vitamin D Status in Type II Diabetes Mellitus Patients - Chowdhury, Tawhida Rahman; Naznin, Lubna; Rahman, S M Mizanur; Mazumder, Md Anayet Karim; Sultana, Nadia (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Along with bone and muscle related morbidities, many other health related disorders have been revealed to be attributed by vitamin D deficiency, among which diabetes is an imperative one. Objective: To present clinical data of serum level of vitamin D in diabetic patients. Methods: A cross sectional study have been conducted over a period of six months from January to June, 2022, among 50 diabetic patients (40 male and 10 female), who reported for follow up investigations in the Department of Biochemistry of Armed Forces Institute of Pathology (AFIP). After availing the approval from the Ethical Review Committee (ERC) of AFIP and informed written consent form the respondent, the data collection was completed through face to face interview and reviewing lab reports. The respondents were checked for their glycemic control in association to their vitamin D status. Results: The mean age of the respondents was 51.6 ±11.1 years. Only 14.0% of them exhibited sufficient level of vitamin D, whereas, D deficiency and vitamin D insufficiency was found in 42.0% and 44.0% respectively. The mean of fasting plasma glucose and HbA1c level found to have statistically significant inverse relation with the mean vitamin D status (p<0.05). Female respondents found to be significantly more prevalent with vitamin D deficiency compared to the male respondents (p<0.05). Conclusion: To reach to more clear conclusions about the favorable effects of vitamin D treatment on T2DM, large scale controlled trials are recommended. This study result suggests that, vitamin D status can be routinely checked in diabetic patients to correct if there is any deficiency. JAFMC Bangladesh, Vol 20, No 1 (June) 2024: 30-33